Complicated pulmonary echinococcosis: XXVI Congreso Uruguayo de Cirugía; coordinador Arnoldo Lischinsky - Lischinsky, Arnoldo; Amorin Cal, Raúl; Méndez Aserito, Hugo; González Maseda, Manuel; Sanjinés Bros, Aníbal (Cirugía del Uruguay, 1975)
Pulmonary Hydatid Echinococcosis (E. H.P.) ranks 29th in frequency, after of hepatic hydatid echinococcosis, and our country being a g, eographic area of extraordinary hydatic infestation, the cited number of observations that are recorded, means that in Uruguay numerous works have been published referring to its clinical pathology, radiology and surgical treatment, which constitute fundamental pillars for its study. At the II Uruguayan Congress of Surgery in 1951, Armand Ugón laid the foundations for the surgical treatment of the E.H.P. and its complications and today, many years later, we see that its conceptual contribution remains valid. The E.H.P. it is complicated, as we will see, with extraordinary frequency, although it has lower mortality rates than the complications of hydatic liver cysts.